Faktor Faktor dalam Pengambilan Keputusan Pembelian Online Jeans Demorin - Syahdina, Aang; Nurmala, Rahmi; Andini, Regina Natasya; Iriawan, Naviri Albert; Rahina, Yulistya Nayla; Alifa, Syafa Nur; Vitasari, Vindry; Mahendra, Rafi Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study updates the idea and influence of product innovation or breakthrough, advertising and evaluation of goods purchased online. Using quantitative methods and purposive sampling, 100 respondents were obtained from a total of 62,572 online transactions throughout 2024. This study proves that product breakthroughs and product evaluations have a good impact on purchasing decisions, on the other hand advertising does not have a big impact, this study provides input to companies to focus on developing new and unique products to improve and increase purchases.